2015
DOI: 10.1080/00343404.2014.985644
|View full text |Cite
|
Sign up to set email alerts
|

A Post-Mortem of Regional Innovation Policy Failure: Scotland's Intermediate Technology Initiative (ITI)

Abstract: The Intermediate Technology Initiative (ITI) was one of the most ambitious 'systemic' regional innovation policy instruments developed in the UK in recent years. However, little of the ITI's anticipated outputs materialised and the programme was prematurely terminated. This paper examines the reasons for its failure which largely centred on the programme's inappropriate design. The findings suggest that greater recognition needs to be given to the specificities of local entrepreneurial ecosystems when designin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 67 publications
(57 reference statements)
1
28
0
Order By: Relevance
“…Amezcua et al, 2013). They have primarily examined the success or failure of individual programs based on the impact they have had on client firms or the larger regional economy (Brown et al, 2015). This ignores the fact that most regions have multiple entrepreneurship programs run by a variety of actors including local governments, universities, economic development agencies, and third sector community groups.…”
Section: Governing Entrepreneurial Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amezcua et al, 2013). They have primarily examined the success or failure of individual programs based on the impact they have had on client firms or the larger regional economy (Brown et al, 2015). This ignores the fact that most regions have multiple entrepreneurship programs run by a variety of actors including local governments, universities, economic development agencies, and third sector community groups.…”
Section: Governing Entrepreneurial Ecosystemsmentioning
confidence: 99%
“…The devolution of economic development responsibilities to the Scottish Government has lead to a major role for public support for technology entrepreneurship in Edinburgh's economy (Keating, 2005, Brown et al, 2015. Scottish Enterprise, the main Scottish economic development organisation, distributed more than £250 million in aid and grants to entrepreneurial ventures in 2014-15, with a particular focus on growth-oriented technology ventures (Scottish Enterprise, 2015).…”
Section: Entrepreneurial Support In Edinburgh Scotlandmentioning
confidence: 99%
“…Interviews revealed that strategic partners may act as buyers or suppliers of the product and services of the start-up firm, or as collaborators. This has a critical role in the knowledge filter, with numerous interviewees reporting that having access to such support provides significant insights concerning market readiness (Mason and Brown, 2013;Brown et al, 2016). However, relationships with strategic partners have not always been seamless, with, for example, some entrepreneurs pointing to challenges in accessing personnel within large firms.…”
Section: Analysis Of the Programmementioning
confidence: 99%
“…Miettinen (2002) suggests that researchers and policy makers have become unhealthily close, to the point that they have become dependent upon -indeed captured by -the other. This is despite concerns about the applicability of the NSI framework and deeper uncertainties about whether attempts to replicate features seen as driving success in one nation, region or sector will succeed elsewhere (Tait & Williams 1999;Brown et al 2016).…”
Section: Nsi and Sts Epistemic System -Tensions Between Research And mentioning
confidence: 99%